Association between 5-item modified frailty index and clinical outcomes in elderly rectal cancer patients after radical surgery - Hong Wu; Feiyu Shi; Chenhao Hu; Lei Zhang; Penghong Qu; Junjun She (Scientific Reports)
Abstract Frailty is a significant factor contributing to an increased risk of adverse clinical outcomes in older cancer patients. This study aims to investigate the impact of the 5-item modified frailty index (mFI) on both short-term and long-term prognosis in elderly rectal cancer patients who underwent radical resection. And, by integrating the 5-item mFI with clinicopathological characteristics, a postoperative severe complications nomogram and a cancer-specific survival (CSS) prediction nomogram were further constructed. Demographic, clinical, and therapeutic data were collected from 1,034 patients aged ≥ 70 years with rectal cancer who underwent proctectomy between 2017 and 2022. Patients were categorized into three groups based on their mFI scores: 318 patients with mFI = 0, 404 patients with mFI = 1, and 312 patients with mFI ≥ 2. Comparisons among these groups revealed that higher 5-item mFI scores were associated with an increased incidence of both overall and severe postoperative morbidity, prolonged recovery times, and elevated total medical costs. Multivariate logistic regression analysis indicated that an mFI score of ≥ 2 [odds ratio = 2.856, 95% confidence interval (CI): 1.542–5.290, P < 0.001] was an independent risk factor for severe postoperative complications. Similarly, in competing risk analysis, the 5-item mFI was identified as an independent prognostic factor for CSS (subdistribution hazard ratio = 2.00, 95% CI: 1.47–2.72, P < 0.001). The postoperative severe complications nomogram and CSS prediction nomogram AUC values were 0.726 and 0.844, respectively, both demonstrating promising predictive capabilities. In conclusion, the 5-item mFI serves as a concise and effective tool for preoperative frailty stratification and for predicting clinical outcomes in elderly rectal cancer patients.